The effect of of oligosaccharides from sweet potato on layers performance - Tuti Haryati; Supriyati . (Jurnal Ilmu Ternak dan Veteriner, 2011)
The investigation was carried out to study the utilization of oligosaccharides from sweet potato as feed additives to improve the performance of laying hens. Oligosaccharides were extracted from sweet potato using 80% ethanol. Extractant and residue were evaluated as feed additive. Ninety six of 18 weeks old laying hens from CP 909 Isa Brown were randomly distributed into four treatments with six replicates and four laying hens per replicate. The treatments were: Ro = Control without oligosaccharides, R1 = R0 + 0.1% of extract of sweet potato. R2 = R0 + with 0.2% of residue of sweet potato, and R3 = R0 +  with 0.2% of commercial FOS. The evaluations were carried out up to 25 weeks of egg production. The data were evaluated with statistical analysis using SAT. The results showed that egg production and FCR of R1 and R2 were better than R0 (P < 0.05). The treatments were not significantly affected feed consumption. In conclusion, addition of extract or residue of sweet potato improved (P < 0.05) egg production and FCR of layers compared to control diet. Key Words: Oligosaccharides, Sweet Potato, Performance, Layers